2019
DOI: 10.1186/s12906-019-2603-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of methicillin-resistant and methicillin-sensitive Staphylococcus aureus susceptibility to Saudi honeys

Abstract: Background: Honey has been increasingly recognized as a potential therapeutic agent for treatment of wound infections. There is an urgent need for assessment and evaluation of the antibacterial properties against wound pathogens of honeys that have not yet been tested. Methods: Ten Saudi honeys collected from different geographical locations were screened initially for their antibacterial potential against methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive Staphylococcus aureus (MSSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
1
2
0
3
Order By: Relevance
“…A minimum inhibitory concentration (MIC, the lowest concentration to inhibit visible growth of bacteria) in the range of 5%−15% w/v was measured for all Manuka grades. Zones of inhibition in the range of 16.0−16.8 mm were produced by 120 µL of a medical grade Manuka honey (MGO 400 mg/kg, 50% w/v dilution in water) in agar well diffusion assays against MRSA and MSSA (Hussain et al, 2019). As comparison, values in the same order of magnitude were recorded for a 30 µg disc of the antibiotic vancomycin (20.5−21.8 mm) against the same pathogens.…”
Section: Electrospinning Of Honeymentioning
confidence: 99%
“…A minimum inhibitory concentration (MIC, the lowest concentration to inhibit visible growth of bacteria) in the range of 5%−15% w/v was measured for all Manuka grades. Zones of inhibition in the range of 16.0−16.8 mm were produced by 120 µL of a medical grade Manuka honey (MGO 400 mg/kg, 50% w/v dilution in water) in agar well diffusion assays against MRSA and MSSA (Hussain et al, 2019). As comparison, values in the same order of magnitude were recorded for a 30 µg disc of the antibiotic vancomycin (20.5−21.8 mm) against the same pathogens.…”
Section: Electrospinning Of Honeymentioning
confidence: 99%
“…Penelitian ini menggunakan metode agar well diffusion, konsentrasi yang digunakan 50% dan 25% dilarutkan dalam air distilasi steril atau aquades. Menghasilkan zona hambat yang bervariasi antara satu madu dengan madu yang lain, dengan zona hambat pada seluruh kelompok konsentrasi 50% lebih besar dari kelompok konsentrasi 25% dengan beberapa sampel madu dari kelompok konsentrasi 25% tidak terdapat zona hambat [8] .…”
Section: Pembahasanunclassified
“…Hasil dari penelitian oleh Hussain tahun 2019 ini mendukung hasil dari penelitian bahwa tidak semua madu dapat menghasilkan zona hambat apabila sudah di larutkan, kemudian dapat pula disimpulkan bahwandiameternzonanhambat bakteri yang terbentuk berbanding lurus dengan peningkatanNkonsentrasi larutanNyang diberikan. Kesimpulan ini dapat ditarik dikarenakan daya hambat bakteri pada Madu Kele Sanjiwani konsentrasi 100% memiliki nilai yang kecil maka kemudian tidak mengherankan apabila kelompok konsentrasi yang lebih kecil tidak menghasilkan zona hambat, hal ini di dukung oleh penelitian oleh Hussain tahun 2019 bahwa semakin kecil konsentrasi maka semakin kecil pula daya hambatnya [8] .…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…It is dark amber or black viscous liquid that is useful in modern medicine for the management of gastrointestinal, cardiovascular, inflammatory, and neoplastic states [16]. Major components of honey include fructose, glucose, amino acids, vitamins, minerals, and enzymes [16][17][18], which work together to provide varying therapeutic effects such as antioxidants [19]; Cardioactive and vasoactive effect [20], and antimicrobial [21][22][23]. It has been reported that oral administration of honey and glucose or fructose showed protection against gastrointestinal diseases such as gastric ulcers [24].…”
Section: Introductionmentioning
confidence: 99%